Mobile city : emerging media, space, and sociality in contemporary Berlin - Kraemer, Jordan H., 1978- (Cornell University Press, 2024)
"In late-aughts Berlin, emerging media, from Facebook to smartphones, reworked place-based identities, facilitating urban, middle-class aspirations to cosmopolitan connection while transforming experiences of everyday life. These scalar transformations were lived out through ordinary practices that reconfigured sociality, mobility, and urban space"--